2019
DOI: 10.1002/cssc.201900500
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Zr Doping in Stabilizing Li[Ni0.6Co0.2Mn0.2]O2 as a Cathode Material for Lithium‐Ion Batteries

Abstract: Ni‐rich layered LiNi1−x−yCoxMnyO2 systems are the most promising cathode materials for high energy density Li‐ion batteries (LIBs). However, Ni‐rich cathode materials inevitably suffer from rapid capacity fading and poor rate capability owing to structural instability and unstable surface side reactions. Zr doping has proven to be an effective method to enhance the cycle and rate performances by stabilizing the structure and increasing the Li+ diffusion rate. Herein, effects of Zr‐doping on the structural stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…7d). The accumulation of internal-strain in undoped SNCM during cycling at the high charging cut-off voltage of 4.6 V is mainly ascribed to responsible for the generation of nanocracks [52][53][54] , and it will impede the Li + diffusion in the sample and cause the structure collapse.…”
Section: Discussionmentioning
confidence: 99%
“…7d). The accumulation of internal-strain in undoped SNCM during cycling at the high charging cut-off voltage of 4.6 V is mainly ascribed to responsible for the generation of nanocracks [52][53][54] , and it will impede the Li + diffusion in the sample and cause the structure collapse.…”
Section: Discussionmentioning
confidence: 99%
“…Related studies have shown that the thermal stability of active materials doped with Zr atoms in the lattice is significantly enhanced. 53 Another work 109 explains the mechanism of Zr 4+ doping used to suppress the phase transition. The atomic resolution TEM images presented in Fig.…”
Section: Investigation On Strategies To Suppress the Degradation Of T...mentioning
confidence: 99%
“…Zhang et al [251] showed that co-doping the TM and O sites with Al 3+ and (PO4) 3respectively reduced cation mixing and improved the overall stability of the cathode and cycling ability, although with a slightly deleterious effect to the initial capacity. Finally, simultaneous Li and O site doping has also been shown to enlarge the interlayer spacing, thus improving Li diffusion and rate capability [235,236].…”
Section: Multiple Site Co-dopingmentioning
confidence: 99%
“…It can prevent extensive lattice parameter change during battery operation, mitigate oxygen evolution and cation migration, thus slowing down surface reconstruction and rapid electrolyte deterioration. Additionally, simultaneous Li and O site doping has been shown to enlarge the interlayer spacing, thus improving Li diffusion and rate capability[235,236].…”
mentioning
confidence: 99%